1995
DOI: 10.1111/j.1748-1716.1995.tb09849.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hypothermia on renal function and haemodynamics in the rat

Abstract: The effects of 1-2 h of hypothermia at 28 degrees C and rewarming on renal function were investigated in anaesthetized rats, using conventional clearance methods and the micropuncture technique. Renal blood flow (RBF) decreased from 7.3 +/- 0.51 mL min-1 at 37.5 degrees C (control) to 4.0 +/- 0.47 at 28 degrees C, with almost complete restoration to 6.9 +/- 0.59 mL min-1 after rewarming. Systemic blood pressure remained essentially unaltered. The RBF reduction seen during hypothermia was due to a 75% increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 11 publications
10
65
0
1
Order By: Relevance
“…The trend towards a reduction in Na plasma concentration could be explained by cold-induced diuresis, reported to occur in mild [5] and moderate [31] hypothermia. Two mechanisms are expected to be responsible for the cold-induced diuresis: (1) hypothermia depresses Na reabsorbtion with consequent diuresis [32], and (2), in a single-nephron model, Broman and Kalskog [31] showed that cold-induced diuresis was due to diminished fluid reabsorbtion in the distal segments of the tubular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend towards a reduction in Na plasma concentration could be explained by cold-induced diuresis, reported to occur in mild [5] and moderate [31] hypothermia. Two mechanisms are expected to be responsible for the cold-induced diuresis: (1) hypothermia depresses Na reabsorbtion with consequent diuresis [32], and (2), in a single-nephron model, Broman and Kalskog [31] showed that cold-induced diuresis was due to diminished fluid reabsorbtion in the distal segments of the tubular system.…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms are expected to be responsible for the cold-induced diuresis: (1) hypothermia depresses Na reabsorbtion with consequent diuresis [32], and (2), in a single-nephron model, Broman and Kalskog [31] showed that cold-induced diuresis was due to diminished fluid reabsorbtion in the distal segments of the tubular system. These authors pointed out, that in the distal segments an antidiuretic hormone (ADH) exerts its influence on the water permeability and suggested that the ADH system may also be responsible for increased diuresis observed in hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…24) In fact, the plasma concentration profile and pharmacokinetic parameters of FD-4 were markedly changed under the hypothermic condition at 28°C (Fig. 6, Table 3).…”
Section: Comparison Of Fd-4 Pharmacokinetics Between the Hypothermic mentioning
confidence: 99%
“…Both HI [14] and HT [6] may lead to necrotising enterocolitis. Posthypoxic renal failure, found in 40% of term infants after perinatal asphyxia [15,16] combined with 'cold diuresis' [17] in response to HT may result in unpredictable changes in electrolyte and fluid balance. Pulmonary hypertension after asphyxia [16] can be further aggravated by mild HT [11,18].…”
Section: Introductionmentioning
confidence: 99%